Pegida-Effekte?: Jugend zwischen Polarisierung und politischer Unberührtheit - Marg, Stine; Schmitz, Christopher; Trittel, Katharina; Schenke, Julian (transcript, 2018)
Pegida has changed the political discourse: this much is clear four years after the protests began. But interpretations of the causes and consequences of "Patriotic Europeans against the Islamization of the Occident" vary widely.Based on an extensive empirical study, the authors of this volume discuss whether and how Pegida catches the youth as a phenomenon of protest and code. The study offers an analysis of young people's political interpretative patterns in 2018 by focusing on political ideas, wishes, fears and thoughts about the democratic immigration society.